(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The analysis of human rights and disputes in the usage, allocation and possession of the land and its properties includes a political geography. These scandals will take place on several levels. They can include neighbors who are struggling to place garden fences properly territorial demands between competing tribes or numerous national groups residing within a single state territorial discrepancies within neighboring States, or global rivalry for power blocs. They may be achieved both within communities and within local groups or groups opposed to tree felling or road development.